The influences of social media on the shopping decision-making styles of selected Filipino generation X - Dela Cruz, Leniniza C. (College of Home Economics, University of the Philippines Diliman, 2016)
Although Generation X has been called the neglected generation, they have a huge influence in the decision-making process of other generations when shopping, and are huge consumers themselves. This generation consumes different types of media: print media that they grew up consuming; and social media that they have recently gotten used to. This study attempted to discover the difference in the shopping decision making styles of Filipino Generation X before and after social media, and whether social media has influenced their shopping decision-making styles. The study surveyed fifty (50) empowered respondents in Metro Manila who regularly consume all forms of media, and were chosen through non probability purposive and snowball sampling. Based on their answers, it was seen that the decision-making style factors they deem important are the same now as they were before. Also, respondents' thought processes while shopping have changed over the years; with social media being one of the factors that influenced the change. The study recommends that the shopping and decision-making styles of Filipino Generation X be studied in further detail and for brands and marketers to formulate effective ways in reaching out to this market.